EVALUACIÓN FINANCIERA PARA LA APERTURA DE UNA SUCURSAL DE LA COOPERATIVA DE AHORRO Y CRÉDITO CACPE - LOJA LTDA. EN EL CANTÓN PALANDA, PROVINCIA DE ZAMORA CHINCHIPE - Jaramillo Ordóñez, Lisbhet Tatiana (2018)
The thesis entitled "Financial evaluation for the opening of a branch of the Credit Union CACPE – Loja Ltda. In the canton of the province of Zamora Chinchipe", is intended to provide a study that allows the opening of a branch of the Cooperativa de Ahorro y credito Cacpe-Loja in the canton of Palanda in order to grant appropriate financial products and services to the reality of the sector. The Canton Palanda is a productive, agricultural and cattle sector for what it is an important aperture a branch of the cooperative of saving and credit Cacpe Loja, this way it was demanded by the market research in which there was obtained a sample of 95 persons and one proceeded to apply the survey to the Population, results that allowed to obtain conclusions and to elaborate recommendations with the intention of determining if it is feasible or not the implementation of the branch of the Cooperative of Saving and Credit "Cacpe Loja" in the Canton Palanda; likewise there decided the unsatisfied demand of the economically active population of the Canton Palanda in which the demand is bigger than the offer, the COAC an investment of $ needs 52.852.06 dollars; in the technical study the ideal size and location decided of the project, in the financial study there were obtained the respective depreciations of the fixed assets and to determine the total investment of the project represented in fixed assets and hereby to determining the financial statements projected to obtain results of the cost of investment obtaining a point of balance of $ 50.203,83 dollars for the first year with an installed capacity of 61,23 %; one will be had THEY GO of $, a TIR of 26 % a RCB of 1,13 $ and the recovery of the investment of the project will be in 2 years, 9 months, 21 days; in the analysis of sensibility it made clear that the costs increase in 0.92 % and the income diminishes in 0.92 % .